FRI0009 Serum 14-3-3 ETA Is An RA Specific Mechanistic Marker. (15th July 2016) - Dasgupta, B.; Cherkas, Y.; Lamberth, S.; Hayden, K.; Brodmerkel, C.; Marotta, A.; Curran, M.
Abstract : Background: 14–3-3η is an emerging soluble Rheumatoid Arthritis (RA) biomarker that activates intracellular pathways that lead to the upregulation of inflammatory and joint damage factors. It is reported to be highly specific and sensitive for RA as a diagnostic marker, higher levels are associated with greater joint damage progression risk and 14–3-3η's modulation with treatment suggests a role in disease monitoring. Objectives: In this study, we examine the specificity of 14–3-3η in an independent, clinically well-characterized cohort of moderate to severe RA and disease control subjects. Methods: Serum 14–3-3η levels were measured in a total of 147 patients using the Augurex 14–3-3η ELISA. The patient set comprised 36 with RA and 111 controls consisting of 20 with asthma (A), 20 with Crohn's Disease (CD), 12 presumed healthy (H), 16 with psoriasis (PsO), 20 with sarcoid arthritis (S), and 23 with spondylarthropathies (SpA). Sample testing was done independently of Augurex. Mann-Whitney testing together with Kruskal-Wallis analysis with the post-hoc Dunn's multiple comparison test was performed to assess group differences. Receiver operator characteristic curve (ROC) analysis was performed to assess the specificity of 14–3-3η for RA. Results: Median (IQR) serum 14–3-3η levels were significantly higher in RA [2.35ng/ml (0.28–19.41)] than all controls [0 (0–0)], p<0.0001. ROC curve analysis further underscored this differential expression yielding a significant area under the curve (AUC) of 0.86, p<0.0001. At the diagnostic positivity cut-off of ≥0.19 ng/ml, the ROC curve delivered a sensitivity of 81% with a corresponding specificity of 84%. Kruskal-Wallis testing revealed that serum 14–3-3η levels were significantly higher in RA in comparison to all other diseases, p<0.0001. Conclusions: Serum 14–3-3η is a highly specific RA biomarker. As a novel mechanistic disease factor, 14–3-3η is expected to provide new insights and approaches to RA management and clinical studies. References: Arthritis Res Ther 2014; 16(2):R99; J Rheumatol 2014; 41(11):2104. Disclosure of Interest: B. Dasgupta Employee of: Janssen R & D, LLC, Y. Cherkas Employee of: Janssen R & D, LLC, S. Lamberth Employee of: Janssen R & D, LLC, K. Hayden Employee of: Janssen R & D, LLC, C. Brodmerkel Employee of: Janssen R & D, LLC, A. Marotta Grant/research support from: Janssen R & D, LLC, M. Curran Employee of: Janssen R & D, LLC